Experience and Expectation During E-Learning of Islamic Religion Education: The Students’ Response - Rabbanie, Muhammad Dahlan; Katni, Katni; Fadil , Khaidir (Utamax : Journal of Ultimate Research and Trends in Education, 2022)
The COVID-19 pandemic has set the stage for alterations to people life in all aspects, including the education aspect. There is a change from traditional learning to e-learning. The changes in learning occur fast and seem sudden in the midst of student mental pressure and lack of preparation. It may cause the expectations of their future learning experiences. The experiences of Islamic Religion Education (PAI) students using e-learning have been the focus of recent quantitative survey-based studies. This study was developed with two objectives: first, to learn about their experience with e-Learning-based Islamic Religion Education (PAI) and then, to reveal their expectations for e-learning. Both were approved using quantitative research that involved disseminating an online poll with 14 closed questions pertaining to 2 questions posed. The sample was purposively selected on 205 out of 1025 students from the Islamic Religious Education Study Program at Ibn Khaldun University Bogor (UIKA) Bogor as respondents by purposive sampling. Because it states the percentage of students participating in e-learning, the simple percentage approach was chosen as 153 respondents to examine the results. The results showed varied learning experiences in PAI-based e-learning, and they expressed the desire that this e-learning learning may continue even in everyday situations. This research can be used as a reference in improving e-learning to increase students' ability to understand the material taught and give convenience in following the learning process.